Rice farmer households' perceptions of rice farming: empirical evidence from Aceh Province, Indonesia - Helmi Noviar; Syahril Syahril (Agriekonomika, 2024)
This article discusses the perceptions of rice farming households towards factors that become constraints in rice farming activities. It emphasizes more on-farm activities on how the dynamics of changes in farmers' perceptions, in the study of rice farming households in Aceh Province. This study uses Aceh Provincial Agricultural Census data for the food crop subsector from 3,353 rice farming households across the province in 2013. The analytical model used is a multivariate probit model, which consists of two dependent variables, i.e., harvest size, and farmer household perceptions. The following table estimates farmer households' perceptions of the various constraints faced that have led to a decline in farmer household productivity. All factors that are the focus of this study are positively perceived by rice farmers. The probability of an expansion of rice harvest area due to the loan factor, the ratio of input prices to output prices and climate change is more than 60 percent. While the perception of farmer households on the availability and wages of farm laborers at 57.7 percent. The implication of several factor’s explaining that capital loans, changes in input and output ratios and climate change on rice farming households is positive any increase in access to loans, improvement in the value of output-input ratios, stability of climate change and farm labor wages will positively affect the probability of increasing the harvest area of rice farming households in Aceh Province.